Demand and supply of cereals in India: 2010-2025 - Ganesh-Kumar, Anand; Mehta, Rajesh; Pullabhotla, Hemant; Prasad, Sanjay K.; Ganguly, Kavery; Gulati, Ashok (International Food Policy Research Institute, 2012)
This paper attempts to project the future supply and demand up to the year 2025 for rice and wheat, the two main cereals cultivated and consumed in India. A review of studies that forecast the supply and demand of Indian agriculture commodities revealed three important limitations of such studies: (a) The forecasts are generally overestimated (in the ex post situation); (b) the methodology is not clearly outlined; (c) ex-ante validation of the forecast have not been carried out. This study presents forecasts based on models that are validated so that forecast performances can be assessed.